Sugar, spice and everything nice: how to end 'sex testing' in international athletics. Issue 4 (2nd October 2017) - Pielke, Roger
ABSTRACT: In many settings, decision makers look to science as the basis for making decisions that are made difficult by their social or political context. Sport is no different. For more than a half century, sports officials have looked to science to provide a clear distinction between men and women for purposes of determining who is eligible to participate in women's athletic competitions. However, the science of sex provides overwhelming evidence that there is no such clear biological demarcation that differentiates men and women. Despite this evidence, the International Olympic Committee and the International Association of Athletics Federations in 2011 implemented a form of 'sex testing' based on androgens, and specifically, testosterone levels in females. This paper evaluates this policy, finding it contradictory to scientific understandings of sex and counter to widely held social norms about gender. The paper recommends an alternative approach to determining eligibility for participation in women's sports events, one more consistent with the stated values of sports organisations, and more generally, with principles of human dignity.